Resiliensi Usaha Cafe di Denpasar pada Masa Pandemi Covid-19 - Wahyu Budi Nugroho; Gede Kamajaya (Jurnal Sosiologi Andalas, 2022)
The aim of this research was to examine the dimensions of the resilience of cafes as a business in Denpasar City during the Covid-19 pandemic. This research adopts a qualitative approach, while the theory that is used as the analytic tool are the theory of resilience, rational choice, and habitus modality. Through research that has been carried out, found out that various cafe strategies in Denpasar City have been found to maintain business continuity during the pandemic, including intensifying promotions on social media, providing discounts and product bundling, holding certain events, and implementing a shift work system for employees. The owners or managers of cafe businesses also seem to optimize the various capitals they have, such as social capital, economic capital, cultural capital, or symbolic capital. The resilience of cafe business owners or managers in Denpasar City is reflected in the dimensions of compensation, dimensions of protection, and their ability to face challenges during the pandemic.